Sensory Acceptance and Nutritional Content of Pumpkin (Cucurbita moschata) and Chayote (Sechium edule) Schotel - Esteria Priyanti; Ira Handayani; Maheswari Nabila Sahda (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
The purpose of this study was 1) to determine the sensory acceptance of Schotel pumpkin and chayote, 2) to know the nutritional content of the most preferred Schotel pumpkin and chayote; and 3) to determine the material composition of the most preferred Schotel. The method applied was the experimental method. The formulas used in this study were product 1 (using 25g pumpkin and 175g chayote), product 2 (using 100g pumpkin and 100g chayote), and product 3 (using 175g pumpkin and 25g chayote). The hedonic test involved 25 untrained panellists. Statistical analysis utilized the Kruskall-Wallis nonparametric and Mann-Whitney follow-up tests at the 95% confidence level (α=0.05). This study's results indicated that the Schotel product using 100g of pumpkin and 100g of chayote was the most preferred and well-accepted product by consumers. Schotel products using 100g of pumpkin and 100g of chayote could meet the energy need by 8%, protein by 17%, fat by 17%, and carbohydrates by 3% per serving. The ingredients composition of the best Schotel product consisted of ingredients A, B, and C. Ingredients A consisted of 350 ml of liquid milk, 100g pumpkin, 100g chayote, 125g ground beef, 100g carrots, 40g onions, 15g garlic, 3 tbsp flour, 1 tsp salt, ½ tsp ground pepper, ½ tsp ground nutmeg, 2 tbsp cooking oil. Ingredients B consisted of 25g of grated cheese and 3 eggs. Ingredients C consisted of 75g of grated cheese.